1973
DOI: 10.1073/pnas.70.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Identity of the Ribosomal Proteins Involved in the Interaction with Elongation Factor G

Abstract: Rabbit antibodies produced against 50 of the 55 individually purified ribosomal proteins of Escherichia coli were tested for their ability to interfere with the formation of the ribosomceEF-G-GDP complex. Only antibodies produced against proteins L7 and L12 inhibited complex formation, and they did so completely.These two proteins were previously shown to be immunologically indistinguishable and necessary for the interaction between ribosomes and EF-G. The present data are consistent with the view that the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…It has been suggested that L7 and L12 constitute a universal GTPase region on the ribosome which may recognize GTP bound to the various soluble factors (37). To date, GTP involvement has been only indirectly implicated in peptidechain termination in vitro using E. coli extracts, and no E. coli ribosomal GTPase activity of RF has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that L7 and L12 constitute a universal GTPase region on the ribosome which may recognize GTP bound to the various soluble factors (37). To date, GTP involvement has been only indirectly implicated in peptidechain termination in vitro using E. coli extracts, and no E. coli ribosomal GTPase activity of RF has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the selective removal of acidic proteins L7 and L12 results in the inhibition of elongation factor-dependent reactions on the ribosome [2-81. Treatment of ribosomes with antibodies against proteins L7 and L12 gave a similar effect [9]. The use of bifunctional cross-linking agents has shown that proteins L7 and L12 are neighbours of the elongation factors when they interact with the ribosome, both for EF-G [lo] and EF-T, [ 111.…”
Section: Introductionmentioning
confidence: 89%
“…As seen in fig.2, the polyphenylalanine synthesis rate with the original (30 S t 50 S) and the 8 Time, min To exclude the possibility of the partial presence of the proteins L7 and L12 in some small active fraction of the extracted ribosomes, a special experiment was done in which the ribosomes were treated with antibodies against proteins L7 and L12. A 50-fold molar excess of the antibodies over the ribosomes was used which induces, according to Highland et al, a 50% inhibition of the translating acitivty of normal ribosomes [9]. The results of the EF-G-dependent poly(U) translation in the system where the 50 S subparticles were treated with antibodies against proteins L7 and L12, and when the antibodies continued to be present in the reaction mixture, are given in table 2.…”
Section: Ef-g-dependent Reactions With Ribosomes Deprived Of Protein mentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of the ribosome are, to a large degree, invested in the protein components of the macrostructure [1][2][3][4][5]. Ribosomal proteins in most procaryotic and eucaryotic cells are basic in ionic character [6].…”
Section: Introductionmentioning
confidence: 99%